Growth and Characterization of an Organic Nonlinear Optical Crystal: 1-Iodo-3-Nitrobenzene (INB) - kumar, S.Vijaya.; Srinivasan, P.; Dinagaran, S.; Balaji, J. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
The 1-Iodo-3-Nitrobenzene crystal was grown by the slow evaporation method from ethanol solvent. The crystalline structure was identified by powder X-ray diffraction (PXRD). The presence of various functional group of the title material was examined by FTIR analysis. The UV-Vis absorption was carried out which shows the fundamental cutoff wavelength around 390 nm and there is no absorption in the entire visible region 390 nm to 1100 nm. The mechanical strength of the grown crystal was measured by Vicker’s microhardness tester. The thermal toughness of the grown crystal was observed by TGA-DTA and DSC studies. The electrical conductivity of the grown crystal is confirmed by dielectric measurement. The nonlinear optical character was assessed by Kurtz-Perry powder technique. This would propose that 1-iodo-3-nitro benzene crystal is a potentially capable in nonlinear optical applications.